Natural radiological risk assessment around archaeological sites, El-Dakhla Oasis (EDO), Egypt - Zakaly, Hesham M. H.; Elsaman, Reda; Kamal, Mohamed; Issa, Shams A. M.; Abbasi, Akbar; Shen, Jinsong; El-Taher, Atef; Yap, Chee Kong; Abdelbaky, Elsayed; Seleem, El-Montser M. (Akademiai Kiado ZRt., 2024)
The natural radionuclides in ancient El-Qasr village located in the El-Dakhla oasis (EDO), Egypt's Western Desert were measured using gamma-ray spectrometry equipped with a NaI (Tl) detector. The findings indicate that the samples' mean activity concentrations were 18.61 ± 1.02, 16.67 ± 0.9, and 137.67 ± 6.9 Bq kg−1 for 226Ra, 232Th, and 40K, respectively. The values of Raeq, D, AED, Hex, Hin, Iγ, and ELCR for the samples ranged anywhere from 34.1 to 83.9 Bq kg−1, 15.7 to 37 nGy h−1, 19.26 to 45.384 Sv y−1, 0.09 to 0.23, 0.12 to 0.23, 0.25 to 0.59, and 6.74E−05 to 1.59E−04, respectively. These values are significantly lower than the international limit of 370 Bq kg−1 for Raeq, 59 nGy h−1 for D, 70 Sv y−1 for AED, 1 for Hex and Hin, 2 for Iγ, and 29E−03 for ELCR. According to the obtained data, none of the samples seemed to be a significant risk when it came to radiation exposure. Using these data, we will determine the baseline level of radionuclides that occur naturally in the area that is the subject of the inquiry.